Determination of an Initial Stage of the Bone Tissue Ingrowth Into Titanium Matrix by Cell Adhesion Model - Liu, Ziyu; Tamaddon, Maryam; Chen, Shen-Mao; Wang, Haoyu; San Cheong, Vee; Gang, Fangli; Sun, Xiaodan; Liu, Chaozong (Frontiers in Bioengineering and Biotechnology, 2021)
For achieving early intervention treatment to help patients to delay or avoid joint replacement surgery, a personalized scaffold should be designed coupling the effects of mechanical, fluid mechanical, chemical and biological factors on tissue regeneration, which results in time-consuming and cost-consuming trial-and-error analyses to investigate in vivo test and related experimental tests. To optimize the fluid mechanical and material property to predict osteogenesis and cartilage regeneration for the in vivo and clinical trial, a simulation approach is developed for scaffold design, which is composed of a volume of fluid (VOF) model for simulating bone marrow filling process of bone marrow and air, as well as a discrete phase model (DPM) and a cell impingement model (CIM) for tracking cells movement during bone marrow fillings. The bone marrow is treated as non-Newtonian fluid rather Newtonian fluid as its viscoelastic property. The simulation results indicated that the biofunctional bionic scaffold with a dense layer to obstacle bone marrow flow out to the cartilage layer and synovia to flow into the trabecular bone area guarantee a well osteogenesis and cartilage regeneration, which match the in sheep vivo test with high accuracy. This approach not only predicts the final bio-performance of the scaffold, it could also enable to optimize the scaffold structure and materials by their biochemical, biological and biomechanical properties.